Terrorism as Communication - Rothenberger, Liane. author. aut Link
XIX, 396 p. 37 illus.
Keywords: Communication theories and terrorism - how can a connection be made here? Terrorism is a dominant topic: It sometimes determines public political discussion as well as private conversations. Communication studies can penetrate the phenomenon of terrorism and provide important pieces of the puzzle to grasp it in its entirety. Moreover, the development of media literacy among some terrorist groups underscores the need to look at the social problem of terrorism from a communication studies perspective. The Author PD Dr. Liane Tessa Rothenberger is a senior lecturer at the Institute for Media and Communication Studies at Ilmenau Technical University. This book is a translation of an original German edition. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation.